Efeito da co-cultura de fibroblastos NIH3T3 e mioblastos C2C12 na expressão da osteoglicina e na migração celular - Cury, Sarah Santiloni [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In mammals, the skeletal muscle growth and regeneration are assigned to process called myogenesis that is regulated, at molecular level, by the interaction of intra and extra-cellular signal transducers. Skeletal muscle differentiation, or myogenesis, is a highly-orchestrated process in which mononucleated muscle precursor cells, the myoblasts, undergo proliferation. Upon differentiation, they withdraw from the cell cycle, migrate, align with each other, and subsequently fuse to form terminally differentiated multinucleated myotubes. Intracellular factors that control this process are already well known, however, recent studies have shown that the myogenic process is highly sensitive and regulated by molecules present in the extracellular medium, even for components secreted by muscle cells (secretome). Recent data from our laboratory demonstrate that among the main components of secretome, the osteoglicina (Ogn) has an important role in myogenesis because the post transcriptional silencing of Ogn by small interfering RNAs (siRNAs) alters the proliferation and differentiation of myoblasts C2C12. Furthermore, Ogn has been described as a major protein secreted by fibroblasts to the extracellular matrix and for presenting function in the aging of heart fibroblasts. Although it is already described certain features of Ogn in fibroblasts or muscle cells, it is still unknown whether the Ogn can participate in one way of communication between these two cell types. Therefore, in this study, we tested the hypothesis that co-culture of fibroblasts NIH3T3 (FB) and myoblasts C2C12 (MB) changes the protein levels of Ogn and consequently myoblast migration. For this, we used the co-cultures FB/MB and MB/MB for 0h, 12h and 24 h to evaluate, in myoblasts, cell migration and protein levels of Ogn. The co-culture FB/MB does not alter the myoblast migration rate; however, it decreased the Ogn protein levels after 12h and...

Em mamíferos, o crescimento do músculo esquelético e sua regeneração são atribuídos ao processo denominado miogênese que, a nível molecular, é regulado pela interação de transdutores de sinais intra e extra-celulares. A miogênese é um processo altamente orquestrado em que células musculares precursoras mononucleadas, os mioblastos, proliferam e diferenciam-se para formação de fibras musculares adultas. Durante a diferenciação, os mioblastos encerram o seu ciclo celular, migram para regiões predeterminadas, alinham-se uns com os outros e, subsequentemente, fundem-se para finalmente se transformarem em miotubos multinucleados. Os fatores intracelulares que controlam esse processo já são bastante conhecidos, entretanto, trabalhos recentes demonstraram que o processo de miogênese é altamente sensível e regulado por moléculas presentes no meio extracelular, até mesmo por componentes secretados pelas células musculares (secretoma). Dados recentes de nosso laboratório demostraram que, dentre os principais componentes do secretoma, a osteoglicina (Ogn) possui uma importante função na miogênese, pois o silenciamento pós transcricional da Ogn por pequenos RNAs de interferência (siRNA) altera a proliferação e a diferenciação dos mioblastos C2C12. Além disso, a Ogn foi descrita como importante proteína secretada por fibroblastos para a matriz extracelular e que apresenta função no envelhecimento de fibroblastos cardíacos. Embora já tenham sido descritas algumas funções da Ogn em fibroblastos ou em células musculares, ainda é desconhecido se a Ogn pode participar de uma via comunicação entre esses dois tipos celulares. Portanto, no presente trabalho, testamos a hipótese de que a co-cultura de fibroblastos NIH3T3 (FB) e mioblastos C2C12 (MB) altera os níveis proteicos da Ogn e, consequentemente a migração de mioblastos. Para isso, utilizamos as co-culturas FB/MB e...
Keywords: Distrofia; Sistema musculoesquelético; Fibroblastos; Dystrophy